Research into application of zeolite for purification of diffusion juice in sugar production - Gusyatinska, Natalia; Nechypor, Tatiana; Gusyatinskiy, Nikolai; Shulga (Zamura), Svеtlana (My University, 2018)
The need to intensify the extraction process using the influence of chemical reagents on beet chips was substantiated. The analysis of application of natural sorbents in food production technologies was carried out. The physical and chemical properties of zeolite were explored. The indicators that make it possible to apply natural zeolite for additional treatment of water and juices in sugar production were shown. The effectiveness of the use of natural zeolite for feed water treatment with the view to enhancing the technological quality of diffusive juice was determined. Experimental research revealed that feed water treatment with zeolite decreases the content of total iron, ammonium, and permanganate oxidation indicator. It was proved that microbial seeding of feed water and diffusive juice decreases in case of treatment with zeolite.It was established experimentally that the purification of diffusion juice occurs during zeolite application for feed water treatment. We determined the effectiveness of removal of macromolecular compounds, including dextran, from diffusive juice obtained during processing sugar beets of various technological quality with natural zeolite. It was shown that at the zeolite consumption of 0,1...0,4 % to the weight of beets, the content of high-molecular compounds and pectic substances in diffusive juice decreases by 30–40 %, and the content of dextran – by 20–40 %, respectively.During the zeolite treatment, an enhancement of the quality of purified juice and im-provement of filtration and saturation properties of defecosaturated precipitate are observed. Thus, the average rate of sedimentation of the precipitate of juice of І carbonation S5 m, when using zeolite for feed water preparation increases by 10–50 % for the beet different technological quality. In the course of research, we designed the technique of zeolite application, which ensures a decrease in coloration, an increase in the purity of the cleared juice, enhancement of filtration and sedimentation properties of the precipitate of juice of I carbonation. High effectiveness of the proposed method is pronounced in processing raw materials of lowered quality. Thus, there are some grounds to claim the effectiveness of zeolite application to enhance the quality of diffusion juice and products in sugar production.
Keywords: diffusion juice; dextran; sucrose extraction; purification of diffusion juice; zeolite; дифузійний сік; декстран; екстрагування сахарози; очищення дифузійного соку; цеоліт; диффузионный сок; экстрагирование сахарозы; очистка диффузионного сока; цеолит; кафедра технології цукру і підготовки води